Ultraviolet Exposure and Photokeratitis Complaints among Informal Welding Workers in Depok, West Java, Indonesia - Yustheresani, Maria K I J; Nurcandra, Fajaria; Fitri, Azizah Musliha; Putri, Annisa Ika; Utari, Dyah (Kesmas, 2020)
One of the photokeratitis risk factors is acute reversible radiation of ultraviolet (UV) rays, which injure the cornea's epithelial tissue. Informal welding workers are susceptible populations to UV rays exposure. This study aimed to confirm the influence of UV radiation exposure on photokeratitis complaints in welding workers in Cimanggis, Depok, West Java. A cross-sectional study was conducted from February to June 2019 and used to select 100 welding workers purposively. A semi-structured questionnaire was used to determine photokeratitis complaints, age, education level, eye protection, safety knowledge, and work period; the UV radiation measured by A UV meter. Data were analyzed using a logistic regression test. We found the proportion of photokeratitis to be 84.0%, with 76.0% of UV radiation exceeding the Threshold Limit Values (TLV). The logistic regression test showed a significant effect of UV radiation on photokeratitis after controlling confounding variables (education level, eye protection, safety knowledge, and welding distance) (p-value = 0.006; AdjOR = 7.236; 95% CI: 1.74–30.07). It can be concluded that UV radiation, more than TLV, constitutes the primary risk factor for photokeratitis complaints. Risks for photokeratitis were influenced by low education level, poor eye protection, limited safety knowledge, and welding distance ≤ 45 cm.